Inside Cover: Mechanism of Carbon Dioxide Adsorption in a Highly Selective Coordination Network Supported by Direct Structural Evidence (Angew. Chem. Int. Ed. 6/2013). Issue 6 (16th January 2013) - Plonka, Anna M.; Banerjee, Debasis; Woerner, William R.; Zhang, Zhijuan; Nijem, Nour; Chabal, Yves J.; Li, Jing; Parise, John B.
<x xml:space="preserve">Abstract</x> Understanding of gas adsorption mechanisms at the molecular level is vital for the rational development of compounds that can remove harmful greenhouse gases from the atmosphere. In their Communication on page 1692 ff., J. Li and J. B. Parise et al. describe the adsorption of CO2 molecules in a "pocket" between two aromatic rings of a nanoporous coordination network. The CO2–framework interaction is characterized by a combination of methods.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>